Public Debt and Fiscal Vulnerability in the Middle East - Soderling, Ludvig (IMF Working Papers; Working Paper ;, 2007)
Public debt in the Middle East increased during the mid-1990s mainly because of fiscal expansions. It decreased in recent years, thanks to high oil revenue, economic growth, some primary non-oil fiscal adjustment, and debt relief. While countries in the Middle East appear to have adequately reacted to high indebtedness in the past, public debt levels remain uncomfortably high in many, particularly non-oil producing countries and middle income oil producers. Non-oil countries adjust mainly by increasing revenues, whereas oil countries adjust expenditure. For non-oil producing countries, substantial fiscal adjustment would be needed to bring debt down to below 50 percent of GDP. Oil producers as a group appear to follow sustainable, though procyclical, fiscal policies. Middle-income (but not high-income) oil producing countries would need to adjust somewhat to bring their policies in line with the permanent oil income benchmark.